IMPROVING PRAGMATIC COMPETENCE OF TECHNICAL UNIVERSITY STUDENTS USING COCA: A CORPUS-BASED APPROACH - Mamajonova, Manzura (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The importance of pragmatic competence in communicative competence has been proved by several researchers and still remained as an issue of the day in the research area. Thus, implementing pragmatic competence in the classroom became significant to enhance the oral and written speech of learners. Improving pragmatic competence demands a great deal from instructors as the young generation’s needs are high. Especially in English for specific purposes, students come across significant difficulties compared to students who learn English as specification. Developments in technology make the education sphere manageable to use various tools in the teaching process. One of them is corpus technology, which is the largest base of texts. COCA (Corpus of Contemporary American English) is one of these corpus technologies and enables learners to compare and contrast the words within text in different contexts. Students of technical universities who become future engineers and IT specialists take the opportunity to improve pragmatic competence using COCA effectively. It enables students to use language appropriately in spoken and written language as it provides students with context and resources from various authentic sources. The aim of this research is to identify the effectiveness of COCA in improving the pragmatic competence of students of technical universities. IT specialists were chosen for this research. The qualitative and quantitative ways of data collection were used to conduct the research and take results. Through experiment, it was clear that usage of COCA significantly contributes to improve pragmatic competence in e-mail writings and communication of students of technical universities.
Keywords: Corpus; pragmatic competence; sociolinguistic competence; linguistics; discourse; context; communication; intercultural; speech act; productive skill; receptive skill